2017
DOI: 10.1111/phn.12346
|View full text |Cite
|
Sign up to set email alerts
|

Exploring collaboration in a community‐academic partnership

Abstract: Findings on how to improve relationship characteristics offer clear suggestions for academic and community partners on ways to move toward collaborative partnerships that can address health inequities and develop a competent and advanced public health nursing workforce in the 21st century.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…These roles can range from being included on institutional review boards, to participant recruitment, and to clinical trial management (Ross et al, 2016). Indeed, such practices have already demonstrated efficacy in several areas of applied sciences including environmental research (Lynn, 2000), public health (Mayer, Braband, & Killen, 2017), and psychological research (Paris et al, 2016). Published guidelines (Ross et al, 2010) exist for implementing such an approach, including for working with indigenous communities (Adams & Faulkhead, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These roles can range from being included on institutional review boards, to participant recruitment, and to clinical trial management (Ross et al, 2016). Indeed, such practices have already demonstrated efficacy in several areas of applied sciences including environmental research (Lynn, 2000), public health (Mayer, Braband, & Killen, 2017), and psychological research (Paris et al, 2016). Published guidelines (Ross et al, 2010) exist for implementing such an approach, including for working with indigenous communities (Adams & Faulkhead, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…[6,10] The benefit of providing new health-related services to the community also ranked favorably on this survey, underscoring that student nurses have the power to introduce new health practices and contribute meaningfully in community settings. A major theme reiterated in our study, and found among other academic community partnerships, is the concept of sharing, defined in a descriptive case study [12] as a, "giving of resources, advice, information and connections between participants through-out the [academic community partnership]." This mutual exchange of resources and labor is critical and a fundamental factor in creating successful academic-community partnerships.…”
Section: Discussionmentioning
confidence: 76%
“…The notion of time as an essential component of authentic learning in community settings has been identified (Mayer et al, ; Wros et al, ). Students within this study clearly spoke to time in place as a critical factor supporting their ability to achieve competency as teachers and managers of chronic disease, experience the first‐hand effects of their interventions and comprehend the complex challenges faced by the populations they were working with.…”
Section: Discussionmentioning
confidence: 99%
“…Current nursing literature demonstrates an increase in notable articles highlighting strengths and challenges of innovative partnerships and academic‐practice partnerships, explicitly. Literature reviews yield articles that discuss model development, project implementation and outcomes, best practices, partner relationships, workforce issues, clinical learning opportunities, anecdotal student value, and advancing research or clinical services (Cygan, McNaughton, Reising, & Reid, ; Glynn, Wendt, McVey, & Vessey, ; Kelly, Abraham, Toney, Muirhead, & Shapiro, ; Larkin, ; Mayer, Braband, & Killen, ; McClure, Lutenbacher, O'Kelley, & Dietrich, ; Schaffer, Schoon, & Brueshoff, ; Wros, Mathew, Voss, & Bookman, ). While authors speak to diverse and innovative collaborative efforts, partnership experiences between distinct programs of nursing to improve population health outcomes are limited (Glynn et al, ; Schaffer et al, ).…”
Section: Introductionmentioning
confidence: 99%